Reciprocal interactions between sodium appetite and need-free sugar intake - Santos, B. M. [UNESP]; David, R. B.; Andrade, C. A.F. [UNESP]; Vendramini, R. [UNESP]; Hurley, S.; Menani, J. V. [UNESP]; Johnson, A. K.; De Luca, L. A. [UNESP] (Elsevier, 2020)
Behavioral sensitization occurs during sodium appetite (expressed as sodium intake to compensate for depleted sodium) and need-free sodium intake (expressed as daily overnight sodium intake in excess of dietary sodium need). Previously, we found that a slow-onset sodium appetite protocol cross-sensitized need-free sucrose intake in sucrose-naïve adult rats. That is, a history of sodium depletion elevated later sucrose intake. The objective of the present work was, first, to investigate whether a protocol that evokes a rapid-onset (within 2 h) sodium appetite using furosemide along with a low dose captopril (Furo/Cap), also cross-sensitizes sucrose intake. Then, we investigated whether 1) sensitization of need-free 0.3 M NaCl intake interacts with need-free sucrose intake, and 2) MK-801, a glutamate NMDA receptor antagonist, inhibits cross-sensitization of sucrose intake. Groups received 3–4 Furo/Cap or vehicle treatments with 48/72-h intervals. We investigated sucrose intake in hydrated and fed conditions for 2 h/day for 5 days, starting 6–10 days after the last Furo/Cap treatment. Episodes of Furo/Cap sensitized need-free sodium intake, as expected. Similar to our prior work, the rapid-onset Furo/Cap protocol cross-sensitized sucrose intake in sucrose-naïve rats and had no persistent effect on blood biochemistry. MK-801 treatment along with Furo/Cap injections appeared to prevent cross-sensitization of sucrose consumption. Sucrose intake tests unexpectedly reduced sensitized need-free sodium intake. However, MK-801 treatment allowed a rebound in need-free sodium intake subsequent to the last sucrose intake test. The results suggest that plasticity in glutamatergic mechanisms mediate inverse and reciprocal interactions between the production of sodium appetite and sucrose intake.
Keywords: Behavioral sensitization; Dehydration; NMDA receptor; Reward; Taste